Open label pilot of personalized, neuroimaging-guided theta burst stimulation in early-stage Alzheimer’s disease - Kashyap, Bhavani; Hanson, Leah R.; Gustafson, Sally K.; Barclay, Terry; Howe, Clarissa M.; Sherman, Samantha J.; Hungs, Marcel; Rosenbloom, Michael H. (Frontiers in Neuroscience, 2024)
BackgroundAlzheimer’s disease (AD) is characterized by cerebral amyloid plaques and neurofibrillary tangles and disruption of large-scale brain networks (LSBNs). Transcranial magnetic stimulation (TMS) has emerged as a potential non-invasive AD treatment that may serve as an adjunct therapy with FDA approved medications.MethodsWe conducted a 10-subject open label, single site study evaluating the effect of functional connectivity-resting state functional MRI guided-approach to TMS targeting with dysfunctional LSBNs in subjects with biomarker-confirmed early-stage AD (https://clinicaltrials.gov/study/NCT05292222). Subjects underwent pre-post imaging and testing to assess connectivity dysfunction and cognition. All participants received intermittent theta burst stimulation [(iTBS), (80% motor threshold; 5 sessions per day; 5 days; 3 targets; 18,000 pulses/day)] over 2 weeks. Three Human Connectome Project (HCP) defined parcellations were targeted, with one common right temporal area G dorsal (RTGd) target across all subjects and two personalized.ResultsWe identified the following parcellations to be dysfunctional: RTGd, left area 8A ventral (L8Av), left area 8B lateral (L8BL), and left area 55b (L55b). There were no changes in these parcellations after treatment, but subjects showed improvement on the Repeatable Battery for the Assessment of Neuropsychological Status attention index (9.7; p = 0.01). No subject dropped out of the treatment, though 3 participants were unable to tolerate the RTGd target due to facial twitching (n = 2) and anxiety (n = 1).ConclusionAccelerated iTBS protocol was well-tolerated and personalized target-based treatment is feasible in early-stage AD. Further sham-controlled clinical trials are necessary to determine if this is an effective adjunctive treatment in early-stage AD.